ZP4 Is Present in Murine Zona Pellucida and Is Not Responsible for the Specific Gamete Interaction - Izquierdo-Rico, Mª José; Moros-Nicolás, Carla; Pérez-Crespo, Míriam; Laguna-Barraza, Ricardo; Gutiérrez-Adán, Alfonso; Veyrunes, Frédéric; Ballesta, José; Laudet, Vincent; Chevret, Pascale; Avilés, Manuel (Frontiers in Cell and Developmental Biology, 2021)
Mammalian eggs are surrounded by an extracellular matrix called the zona pellucida (ZP). This envelope participates in processes such as acrosome reaction induction, sperm binding, protection of the oviductal embryo and may be involved in speciation. In eutherian mammals, this coat is formed of three or four glycoproteins (ZP1 to ZP4). While Mus musculus has been used as a model to study the ZP for more than 35 years, surprisingly, it is the only eutherian species in which the ZP is formed of three glycoproteins Zp1, Zp2, and Zp3, Zp4 being a pseudogene. Zp4 was lost in the Mus lineage after it diverged from Rattus, although it is not known when precisely this loss occurred. In this work, the status of Zp4 in several murine rodents was tested by phylogenetic, molecular, and proteomic analyses. Additionally, assays of cross in vitro fertilization between three and four ZP rodents were performed to test the effect of the presence of Zp4 in murine ZP and its possible involvement in reproductive isolation. Our results showed that Zp4 pseudogenisation is restricted to the subgenus Mus, which diverged around 6 MYA. Heterologous in vitro fertilization assays demonstrate that a ZP formed of four glycoproteins is not a barrier for the spermatozoa of species with a ZP formed of three glycoproteins. This study identifies the existence of several mouse species with four ZPs that can be considered suitable for use as an experimental animal model to understand the structural and functional roles of the four ZP proteins in other species, including human.